2020
DOI: 10.1038/s42003-020-0946-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional culture and in vitro genetic and small-molecule manipulation of adult mouse cardiomyocytes

Abstract: Primary adult cardiomyocyte (aCM) represent the mature form of myocytes found in the adult heart. However, culture of aCMs in particular is challenged by poor survival and loss of phenotype, rendering extended in vitro experiments unfeasible. Here, we establish murine aCM culture methods that enhance survival and maintain sarcomeric structure and Ca 2+ cycling to enable physiologically relevant contractile force measurements. We also demonstrate genetic and small-molecule manipulations that probe mechanisms un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…All experimental procedures involving animals were approved by the University of Toronto Animal Use and Care Committee; all animal experiments were conducted in accordance with the animal care guidelines. Adult mouse ventricular cardiomyocytes were isolated from adult male 6–8 week old CD1 mice (Jackson Labs) 46 , 47 . The outbred CD1 mouse strain was used due to their genetic diversity, larger litter size, and we have used these stains in our ongoing research programs where we have refined cardiomyocyte isolation from CD1 mouse hearts for in vitro genetic and small-molecule manipulation in our lab 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experimental procedures involving animals were approved by the University of Toronto Animal Use and Care Committee; all animal experiments were conducted in accordance with the animal care guidelines. Adult mouse ventricular cardiomyocytes were isolated from adult male 6–8 week old CD1 mice (Jackson Labs) 46 , 47 . The outbred CD1 mouse strain was used due to their genetic diversity, larger litter size, and we have used these stains in our ongoing research programs where we have refined cardiomyocyte isolation from CD1 mouse hearts for in vitro genetic and small-molecule manipulation in our lab 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Adult mouse ventricular cardiomyocytes were isolated from adult male 6–8 week old CD1 mice (Jackson Labs) 46 , 47 . The outbred CD1 mouse strain was used due to their genetic diversity, larger litter size, and we have used these stains in our ongoing research programs where we have refined cardiomyocyte isolation from CD1 mouse hearts for in vitro genetic and small-molecule manipulation in our lab 47 . Briefly, mice were euthanized with isoflurane and hearts perfused with EDTA buffer containing 15 μmol/L of blebbistatin with the heart clamped at the ascending aorta, followed by tissue digestion with collagenase type II (525 units/mL; Worthington Biochemical Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, recent efforts have focused on improving isolation protocols to improve cell yield and lowered the damage to the cardiac tissue ( Guo et al, 2018 ). Notably, Callaghan et al ( Callaghan et al, 2020 ) have shown that Geltrex and blebbistatin using adult mouse cardiomyocytes enhanced survival in culture with maintained cellular function. However, the inhibition of cardiomyocyte contraction using blebbistatin may limit the model’s use to study cardiomyocyte contractility.…”
Section: Animal/human Isolated Adult Cardiomyocytementioning
confidence: 99%
“…A final limitation of our study is that we did not perform contractility or Ca 2+ transient measurements using primary cardiomyocytes isolated from our study mice to determine if the increase in cardiac SERCA2a activity led to relevant changes in cardiomyocyte function in SIRT3 TG mice that were not detectable with echocardiography. The isolation of primary cardiomyocytes from the adult mouse heart and subsequent measurements of contractile force and Ca 2+ transients is possible, but technically challenging (Callaghan et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%